Sintering Properties of ZrO2(MexOy) Fine Powders Produced by Different Methods; Russian Physics Journal; Vol. 67, iss. 8 - Yang Xiao; Burlachenko A. G. Aleksandr Gennadjevich; Buyakova S. P. Svetlana Petrovna (2024, 2024)
Title screen